ANALISIS KEMAMPUAN KEUANGAN DAERAH DALAM MENDUKUNG PELAKSANAAN OTONOMI DAERAH DI KABUPATEN GUNUNG MAS - Septa Soraida (CV. ALIM'SPUBLISHING, 2023)
This study aims to determine the financial performance of the Gunung Mas district government. The performance indicators used in this study are fiscal decentralization, dependency ratios and regional financial independence ratios. The data used in this research is secondary data obtained from the Regional Revenue and Expenditure Budget of the Gunung Mas district government for 2019-2022. The analytical tool used in this study is descriptive analysis using the ratio of fiscal decentralization, the ratio of regional financial dependency and the ratio of regional financial independence. The results of the analysis show that the degree of fiscal decentralization of Gunung Mas district is in the low category, the dependency ratio is in the very high category and the independence ratio is very low